Humification and greenhouse gas emissions divergently regulated during black soldier fly manure composting system by biochar, humic acid, and tea residue - Nanyi Wang; Ben Zhang; Wenjuan He; Hongmei Yin; Man Yu; Binghua Yan; Liuqin He; Lin Luo; Xi He; Lihua Zhang; Xichen Zhao; Xing Peng; et al. (Bioresource Technology, 2026)

Divergent impacts of additives on biological risks associated with antibiotic resistance genes during black soldier fly manure composting: A comparative study of biochar, humic acid, and tea residue amendments - Nanyi Wang; Tingzhen Xu; Wenjuan He; Genyi Wu; Xinping Li; Xiaomei Yang; Hongmei Yin; Lin Luo; Lihua Zhang; Liuqin He; Anwei Chen; Man Yu; et al. (Journal of Hazardous Materials, 2026)

Association between residential greenness exposure and excessive gestational weight gain: A dual-center birth cohort study - Xuejin Li; Yanshen Zhang; Yijun Liu; Xiuping Dou; Man He; Yao Huang; Yang Su; Bingying Zhang; Weidong Luo; Qingmei Lin; Yongjun Shi; Boyi Yang; et al. (Environmental Research, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Clathrin-mediated endocytosis governs CdS nanoparticle internalization in rice (Oryza sativa L.) roots - Xinxing Nie; Yili Luo; Langlang Li; Lijuan Xie; Qingqi Lin; Chao Jin; Man Zhao; Kengbo Ding; Hua Qi; Rongliang Qiu (Journal of Hazardous Materials, 2025)

Synergistic effects of biochar-microbial inoculants on greenhouse gas mitigation in paddy ecosystems: organic substitution and enzyme driven emission reduction - Kun Zhou; Keqi Zhao; Xiaobing Zhang; Jiachao Zhang; Man Yu; Liuqin He; Lin Luo; Fangying Yu; Lihua Zhang; Xichen Zhao (Biocatalysis and Agricultural Biotechnology, 2025)

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Evaluation of the Effect of Floating Treatment Wetlands Planted with Sesuvium portulacastrum on the Dynamics of Dissolved Inorganic Nitrogen, CO2, and N2O in Grouper Aquaculture Systems - Shenghua Zheng; Man Wu; Jian Liu; Wangwang Ye; Yongqing Lin; Miaofeng Yang; Huidong Zheng; Fang Yang; Donglian Luo; Liyang Zhan (Journal of Marine Science and Engineering, 2025)
Aquaculture expansion to meet global protein demand has intensified concerns over nutrient pollution and greenhouse gas (GHG) emissions. While floating treatment wetlands (FTWs) are proven for water quality improvement, their potential to mitigate GHG emissions in marine aquaculture remains poorly understood. This study quantitatively evaluated the dual capacity of Sesuvium portulacastrum FTWs to (a) regulate dissolved inorganic nitrogen (DIN) and (b) reduce CO2/N2O emissions in grouper aquaculture systems. DIN speciation (NH4+, NO2−, NO3−) and CO2/N2O fluxes of six controlled ponds (three FTW and three control) were monitored for 44 days. DIN in the FTW group was approximately 90 μmol/L lower than that in the control group, and the water in the plant group was more “oxidative” than that in the control group. The former groups were dominated by NO3−, with lower dissolved inorganic carbon (DIC) and N2O concentrations, whereas the latter were dominated by NH4+ during the first 20 days of the experiment and by NO2− at the end of the experiment, with higher DIC and N2O concentrations on average. Higher primary production may be the reason that the DIC concentration was lower in the plant group than in the control group, whereas efficient nitrification and uptake by plants reduced the availability of NH4+ in the plant group, thereby reducing the production of N2O. A comparison of the CO2 and N2O flux potentials in the plant group and control group revealed that, in the presence of FTWs, the CO2 and N2O emissions decreased by 14% and 36%, respectively. This showed that S. portulacastrum FTWs effectively couple DIN removal with GHG mitigation, offering a nature-based solution for sustainable aquaculture. Their low biomass requirement enhances practical scalability.

High-resolution estimation of urban anthropogenic carbon emissions - Zirong Lin; Bo Huang; Jia He; Yizhen Yan; Man Xiao; Qinrui Luo; Zhulin Qi; Xiaotian Ding (Sustainable Cities and Society, 2025)

The Guanylate Cyclase Soluble Subunit Alpha-1 Deficiency Impairs Angiogenesis in Zebrafishes and Mice: In Vivo and In Vitro Studies - Man Luo; Dongcan Mo; Jianli Li; LiuYu Liu; Xiaoling Li; Jing Lin; Jie Liang; Fei Ye; Xiaozuo Lin; Pingkai Wang; Xiaoju Wu; Yinan Zeng; et al. (Molecular Neurobiology, 2025)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Konjac glucomannan/xanthan synergistic interaction gel: Effect of the fine structure of xanthan on enthalpy driven assembly behavior and gel strength - Dongling Qiao; Yishen Li; Man Luo; Fayin Ye; Lisong Lin; Fatang Jiang; Guohua Zhao; Binjia Zhang; Fengwei Xie (Food Hydrocolloids, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Model test on support scheme for carbonaceous slate tunnel in high geostress zone at high depth - Zhi-gang Tao; Shu-lin Ren; Gan Li; Hao-tian Xu; Sen-lin Luo; Man-chao He (Journal of Mountain Science, 2021)

Prevalence of RNF213 variants in symptomatic intracranial arterial stenosis/occlusion in China - Xunsha Sun; Man Luo; Jiaoxing Li; Rong Lai; Jing Lin; Yufang Wang; Xiaowei Xu; Shaoqing Wu; Wenli Sheng (Molecular Genetics and Genomics, 2020)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Heat stress impairs mice granulosa cell function by diminishing steroids production and inducing apoptosis - Man Luo; Lian Li; Cheng Xiao; Yu Sun; Gen-Lin Wang (Molecular and Cellular Biochemistry, 2016)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

Marinobacter shengliensis sp. nov., a moderately halophilic bacterium isolated from oil-contaminated saline soil - Yi-Jing Luo; Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Ya-Nan Wang; Heng-Lin Cui; Hua Cai; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Increased risk of colorectal malignant neoplasm in patients with nonalcoholic fatty liver disease: a large study - Xian-Feng Lin; Ke-Qing Shi; Jie You; Wen-Yue Liu; Ying-Wan Luo; Fa-Ling Wu; Yong-Ping Chen; Danny Ka-Ho Wong; Man-Fung Yuen; Ming-Hua Zheng (Molecular Biology Reports, 2014)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)